KAJIAN HABITAT TUMBUHAN OBAT DI TAMAN WISATA ALAM CAMPLONG - Blasius Paga; Yosefus F. da-Lopes (Partner, 2008)
Study on Medical Plants Habitat in Taman Wisata Alam Camplong. The research aimed to find out the habitat condition of medical plants in Taman Wisata Alam Camplong covering, structure and composition of vegetation, as well as accentual and threat to the medical plants habitat. Collecting data of medical plants habitat covered habitat type, structural and composition of vegetation and accentual/threat to habitat of the plants. Those data were obtained through stocktaking and were analyzed using vegetation analysis. Samples were acquired at line plot of 20 x 1000 m. The line plot, hereinafter, was divided into smaller, depended on growth level and life model of the plants observed. Data of INP (Indeks Nilai Penting = Important Value Index) was to know type of dominant plant (Soerianegara and Indrawan, 1998). The results indicated that habitat type in the area of TWA Camplong included semi fall forest. The highest INP of tree was 42,4884 at taduk (Alstonia scholaris), while, the lowest INP was at papi (wild sandalwood), that is 0,8538. Reviews on licensed online casinos ,bonuses from the online casinos. In level of pillar, the highest INP was 46,3083 at guava species, and the lowest was 2,4062 at haubiabnapa, tati'i, nangkelo. In the stake level, the highest INP was 40,8617 at bamboo and the lowest INP was 2,1032 at haumanikin. In seedling level, the highest Â INP was 90,4850 at kirinyu (Chromolena odorata); while, the lowest INP was at talas (INP = 0,9561).Keywords: TWA Camplong, medical plant, habitat, INP